The timeless perspective vs. discretion: theory and monetary policy implications for an open economy - Alfred V. Guender (Deutsche Bundesbank, 2007)
This paper proposes an open-economy Phillips Curve that features a real exchange rate channel. The resulting target rule under optimal policy from a timeless perspective (TP) involves additional history dependence in the form of lagged inflation. The target rule also depends on the discount factor as well as IS and Phillips Curve parameters. This is in sharp contrast to a closed economy where the target rule depends only on the change in the output gap, the current rate of inflation and the structural parameter in the Phillips Curve. Because of the additional history dependence in an open economy, price level targeting is no longer consistent with optimal policy. If a real exchange rate channel does not exist in the Phillips Curve, monetary policy eases in the wake of a positive cost-push disturbance under policy from a TP and is thus diametrically opposed to same under discretion. Maximum gains accrue from commitment relative to discretion in an open economy where the real exchange rate is absent from the Phillips Curve and the policymaker places strong emphasis on maintaining price stability.
Keywords: E52; F41; 330; Timeless Perspective; Discretion; Price Level Targeting; Exchange Rate Channel; Geldpolitik; Offene Volkswirtschaft; Regelgebundene Politik; Diskretionäre Politik; Phillips-Kurve; Inflation Targeting; Theorie